Vertical integration for full outsourcing: growth and internationalization of a portuguese packaging firm - Ferreira, Manuel Portugal (2007)
Based on a case study of a Portuguese packaging firm, this paper examines how vertical integration of the supplier serves as a vehicle for the full outsourcing of the client firms' needs in a solution that reduces transaction costs, favors specialization, and permits small and mediumsized firms to develop competencies that may be exploited in a wide array of projects. Vertical integration by the supplier (a governance decision) is a strategic response to changes in the sourcing model of the clients. Client-supplier relationships have inter-spatial and inter-temporal value that surpasses spot market exchanges.